2014
DOI: 10.1007/s10533-014-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of biogenic sulphides in the water column of an acidic pit lake: biogeochemical controls and effects on trace metal dynamics

Abstract: Production of H 2 S by bacterial sulphate reduction in the water column of Cueva de la Mora pit lake (SW Spain) may favour an important selfmitigating capacity with respect to metal pollution. The interaction of bacterially produced H 2 S with dissolved metal(loid)s provokes the precipitation of various sulphides, which in turn form a 10 m-thick turbidity layer below the redoxcline. The main goal of this study was to identify the main factors driving the formation of these sulphide precipitates and their impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 63 publications
3
38
0
Order By: Relevance
“…Copper sulfide, for example, is far less soluble than ferrous sulfide (respective log K sp values of −35.9 and −18.8) and therefore CuS precipitates at pH 2, whereas FeS needs much higher pH to precipitate. Diez-Ercilla et al [ 31 ] have also demonstrated that selective precipitation of metal sulfides occurs naturally in Cueva de la Mora pit lake (SW Spain) and the geochemical calculations match perfectly with the results of chemical and mineralogical composition. Ňancucheo and Johnson [ 3 ] showed that it was possible to selectively precipitate stable metal sulfides in inline reactor vessel testing two synthetic AMDs in acidic conditions (pH 2.2–4.8).…”
Section: Remediation Of Acidic Mine Watermentioning
confidence: 61%
“…Copper sulfide, for example, is far less soluble than ferrous sulfide (respective log K sp values of −35.9 and −18.8) and therefore CuS precipitates at pH 2, whereas FeS needs much higher pH to precipitate. Diez-Ercilla et al [ 31 ] have also demonstrated that selective precipitation of metal sulfides occurs naturally in Cueva de la Mora pit lake (SW Spain) and the geochemical calculations match perfectly with the results of chemical and mineralogical composition. Ňancucheo and Johnson [ 3 ] showed that it was possible to selectively precipitate stable metal sulfides in inline reactor vessel testing two synthetic AMDs in acidic conditions (pH 2.2–4.8).…”
Section: Remediation Of Acidic Mine Watermentioning
confidence: 61%
“…The accumulated metals may then be harvested and processed to allow metal recovery (Minoda et al, 2015;Raikova et al, 2016). Alternatively, highly acid and metal tolerant microalgae such as the PM01 strain, may have an important role in sustaining SO 4 -reducing bacteria by providing organic carbon and thus increasing the efficiency of AMD remediation microbial bioreactors (Diez-Ercilla et al, 2014;Ňancucheo and Johnson, 2012;Totsche et al, 2006). For example, it was demonstrated that microalgal addition to mine tailing mesocosms containing pyrite-oxidizing bacteria caused higher production of alkalinity, higher concentrations of ferrous Fe, and increased immobilization of Cu and Zn (N ancucheo and Johnson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the anoxic bottom layer of these lakes, in which the absence of Fe(III) (omnipresent in oxidizing environments) allows detailed study of the geochemical behavior of other important dissolved substances such as Al or SiO 2 (aq.) (Diez‐Ercilla et al., ; Sánchez‐España et al., ). The special geochemical conditions of these anoxic environments include very high ionic strengths ( I e = 0.5–0.7), salinity close to seawater (36–37‰, mainly caused by SO 4 2− , Fe 2+ and Mg 2+ , instead of Na + and Cl − ), extreme concentrations of dissolved metals (Table S1) and carbon dioxide (up to 5 g/L; Sánchez‐España et al., ), and a pH slightly above 4.0, which is close to the typical pH for Al precipitation in these environments (Figure S1).…”
Section: Geochemical and Microbiological Frameworkmentioning
confidence: 99%
“…We focused on Herrerías‐Guadiana (GUA) and Cueva de la Mora (CM), two well‐characterized acidic pit lakes in SW Spain whose biogeochemistry and limnology have been extensively studied (Diez‐Ercilla, Sánchez‐España, Yusta, Wendt‐Potthoff, & Koschorreck, ; Falagán & Johnson, ; Falagán, Sánchez‐España, & Johnson, ; Sánchez‐España, Boehrer, & Yusta, ; Sánchez‐España, Diez, & Santofimia, ; Sánchez‐España, Yusta, & Diez, ; Sánchez‐España et al., ; Wendt‐Potthoff, Koschorreck, Diez, & Sánchez‐España, ). These artificial lakes formed after the flooding of abandoned metal mine pits of the “ Iberian Pyrite Belt ” mining district and represent unrivaled natural laboratories for the study of biogeochemical processes at extremely acidic conditions (e.g., Sánchez‐España et al., , ).…”
Section: Geochemical and Microbiological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation